Mauriac syndrome in adult with type 1 diabetes mellitus - Natalya Alexandrovna Molitvoslovova; Alla Yur'evna Tokmakova (Сахарный диабет)
We describe the case of Mauriac syndrome in young adult with prolonged poorly controlled type 1 diabetes mellitus.